PENGARUH PERGANTIAN ANGGOTA DIREKSI TERHADAP RENDAHNYA BEBAN PENELITIAN DAN PENGEMBANGAN : PENGUJIAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL INDEPENDEN DAN VARIABEL MODERATING (Studi Pada 10 Perusahaan Go Public) - Irma Lutfiana; Endang Kiswara (Diponegoro Journal of Accounting, 2012)
This study aims to analyze the relationship between the turnover member of directors with the research and development expenditures, to testing the ownership as independent variables and moderating variables. This research refers to research conducted by Graber (2003). There are differences between this study with research conducted by Graber (2003). In their study, Graber (2003) did not conduct testing of managerial ownership, but in his study, Graber (2003) reveals a theory which states that ownership can alleviate negative influence between the turnover member of directors and research and development expenditures. Based on the theory of managerial ownership tested as moderating variables. In connection with the theory expressed by Graber (2003), the test is also performed managerial ownership as an independent variable that refers to the study Cho (1992). This is to test whether managerial ownership is the independent variable or moderating variables in the relationship between the turnover member of directors with research and development expenditures. The research was conducted by quantitative methods on the financial statements of listed companies in Indonesia Stock of Exchange during the period 2007-2011. Total sample is 10 firms, determined by purposive sampling method. The method of testing hypotheses using multiple regression test. The results in line with those performed by Graber (2003), which showed a negative and not significant correlation between turnover member of directors with research and development expenditures. The results also showed that both managerial ownership is not as independent variables and the variables moderating the negative relationship between turnover member of directors and research and development expenditures.